Answer :



(3y)2 - 2 × 3y × 4 + (4)2 - (4)2 + 2 = 0

(3y)2 - 2 × 3y × 4 + (4)2 - 16 + 2 = 0

(3y - 4)2 - 14 = 0

(3y - 4)2 = 14

3y - 14 = ±√14

3y = 14 ± √14

y = (14 ± √14)/3 

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Attempt any threeMaharashtra Board - Algebra Papers

Attempt any threeMaharashtra Board - Algebra Papers

Attempt any five Maharashtra Board - Algebra Papers

Solve the followiMHB - Mathematics Part-1

Solve the followiMHB - Mathematics Part-1

Solve the followiMHB - Mathematics Part-1

Solve the followiMHB - Mathematics Part-1

Solve the followiMHB - Mathematics Part-1

Solve the followiMHB - Mathematics Part-1